2016
DOI: 10.3109/13697137.2016.1149809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on the auditory discrimination task in perimenopausal women: a preliminary study

Abstract: Background The climacteric phase of menopausal transition (perimenopause) is marked by reproductive hormone fluctuations and reduced cognitive capacity. Exercise enhances neurocognitive performance. However, auditory perceptual sensitivity has not been examined. Purpose This study aimed to determine the effect of aerobic exercise on the response speed (reaction time) and error rate during auditory processing among perimenopausal women. Methods Three pitches (500, 1000, and 2000 Hz) were used during a simple au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Of the projections from the inferior colliculus to the thalamus (involved in somatosensory integration and motor control), 40% are GABAergic [ 62 , 63 ]. Known mostly for the relaying of sonic information, the inferior colliculus has also been speculated to be involved in the integration of multimodal sensory integration (including visual information), attention, and reflexes, thus supporting the findings on decreased reaction times reported above [ 62 , 64 , 65 , 66 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Of the projections from the inferior colliculus to the thalamus (involved in somatosensory integration and motor control), 40% are GABAergic [ 62 , 63 ]. Known mostly for the relaying of sonic information, the inferior colliculus has also been speculated to be involved in the integration of multimodal sensory integration (including visual information), attention, and reflexes, thus supporting the findings on decreased reaction times reported above [ 62 , 64 , 65 , 66 ].…”
Section: Discussionsupporting
confidence: 69%
“…Studies have shown that exercise has an influence on reactions to auditory cues in humans and animals, with most evidence pointing to post-exercise improvements in auditory reactions. Aerobic exercise has been shown to improve reaction times and decrease errors in auditory discrimination tasks in perimenopausal women [ 66 ]. A 2013 study found that, among 50 healthy adult subjects, regular aerobic exercise significantly decreased reaction times in an audio-cued labeling task compared to controls who did not exercise regularly [ 65 ].…”
Section: Discussionmentioning
confidence: 99%